2016
DOI: 10.1007/s00125-016-3947-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia reduces ER-to-Golgi protein trafficking and increases cell death by inhibiting the adaptive unfolded protein response in mouse beta cells

Abstract: Aims/hypothesis Hypoxia may contribute to beta cell failure in type 2 diabetes and islet transplantation. The adaptive unfolded protein response (UPR) is required for endoplasmic reticulum (ER) homeostasis. Here we investigated whether or not hypoxia regulates the UPR in beta cells and the role the adaptive UPR plays during hypoxic stress. Methods Mouse islets and MIN6 cells were exposed to various oxygen (O 2 ) tensions. DNA-damage inducible transcript 3 (DDIT3), hypoxia-inducible transcription factor (HIF)1α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 54 publications
5
52
0
Order By: Relevance
“…In contrast to the NICCs in normoxic conditions, there was a marked reduction in the viability and function of NICCs after exposure to hypoxia in our study. Beta cells are sensitive to hypoxic stress because their function depends heavily on the acceleration of mitochondrial metabolism upon glucose stimulation to generate ATP . As a result, hypoxia indeed compromises the viability and function of islets .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the NICCs in normoxic conditions, there was a marked reduction in the viability and function of NICCs after exposure to hypoxia in our study. Beta cells are sensitive to hypoxic stress because their function depends heavily on the acceleration of mitochondrial metabolism upon glucose stimulation to generate ATP . As a result, hypoxia indeed compromises the viability and function of islets .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported some disadvantages for MSCs‐based therapy, such as poor survival, limited differentiation, and dedifferentiation of cells with passaging and donor site, which limits the clinical application of MSC therapy. Therefore, some studies have turned more attention to the concept of cell‐free therapy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparably, exposure of human diploid fibroblasts or HeLa cells to hypoxia led to phosphorylation of eIF2a and ATF4 induction in a PERK-dependent manner (Koumenis et al 2002;Blais et al 2004). Increase in Ddit3 expression during experimental hypoxia has as well been reported to occur, for example, in mouse islets cells (Bensellam et al 2016) and cardiomyocytes (Gao et al 2016). This is, however, to the best of our knowledge, the first report showing ISR induction caused by 'chemical hypoxia', and linking this induction to the KEAP1/NRF2 pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Increase in Ddit3 expression during experimental hypoxia has as well been reported to occur, for example, in mouse islets cells (Bensellam et al . ) and cardiomyocytes (Gao et al . ).…”
Section: Discussionmentioning
confidence: 99%